2019
DOI: 10.1007/s11901-019-00450-8
|View full text |Cite
|
Sign up to set email alerts
|

Portal Hypertension after Liver Transplantation—Causes and Management

Abstract: Purpose of Review While portal hypertension (PHT) treatment strategies for patients with advanced chronic liver disease (ACLD) are well established, studies on the management of PHT after orthotopic liver transplantation (OLT) are limited. This is due to the heterogeneous causes of portal hypertension in the OLT setting. Recent Findings Specific recommendations for the management of non-alcoholic steatohepatitis (NASH), including medical and surgical therapeutic options, and hepatitis C virus (HCV) infection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…This series indicates that, even in technically challenging cases, excellent results are achievable in highly specialised centres. Since end-toend anastomosis was feasible in 96% of patients who underwent liver transplantation in the latter series, this report also suggests that pre-transplant recanalisation of the porto-splenomesenteric axis may decrease the need for surgical recanalisation or non-physiological PV reconstruction at the time of liver transplantation, 107 and thus, may even improve post-transplant outcomes.…”
Section: Tips For Pvtmentioning
confidence: 69%
“…This series indicates that, even in technically challenging cases, excellent results are achievable in highly specialised centres. Since end-toend anastomosis was feasible in 96% of patients who underwent liver transplantation in the latter series, this report also suggests that pre-transplant recanalisation of the porto-splenomesenteric axis may decrease the need for surgical recanalisation or non-physiological PV reconstruction at the time of liver transplantation, 107 and thus, may even improve post-transplant outcomes.…”
Section: Tips For Pvtmentioning
confidence: 69%
“…In terms of long-term outcomes of NASH LT recipients, survival rates are comparable to other etiologies despite the fact that Malik et al [ 127 ] found an alarming 50% 1-year mortality rate among obese NASH patients ≥ 60 years old with T2DM and arterial hypertension[ 127 ]. Thus, pre-transplant work-up warrants extensive risk-benefit evaluation on a case-to-case basis before listing for LT to avoid unexpected complications[ 128 ].…”
Section: Obesity and Mafld/nash Before And After Ltmentioning
confidence: 99%